Transcriptional Analysis of the Bordetella Alcaligin Siderophore Biosynthesis Operon - Kang, Ho Young; Armstrong, Sandra K. (East Carolina University, 1998)
The alc gene cluster of Bordetella pertussis includes three genes, alcA, alcB, and alcC, which are involved in alcaligin siderophore biosynthesis in response to iron starvation. The production of AlcA, AlcB, and AlcC in Bordetella cells and the transcriptional organization of alcA, alcB, and alcC were investigated by using a set of three alc*-*lacZ gene fusion constructs that were contiguous with the known promoter upstream of alcA and extended to fusion junctions within each alc cistron. All three alc*-*lacZ fusions exhibited iron-repressible reporter gene expression which was abolished by deletion of the 105-bp alcA promoter-operator region. In an immunoblot analysis using a monoclonal antibody specific for b-galactosidase, the AlcA-LacZ, AlcB-LacZ, and AlcC-LacZ hybrid proteins were detected in Bordetella cells grown under iron-depleted conditions. A B. pertussis mutant in which the 105-bp alcA promoter-operator region was deleted by allelic exchange was unable to produce detectable levels of siderophore. Hybridization analysis using gene-specific probes showed that alc-specific transcript levels in the mutant were negligible compared with those of the wild-type parent. These results confirm that alcA, alcB, and alcC are cotranscribed from an iron-regulated control region immediately upstream of alcA. Transcript analysis using hybridization probes representing regions downstream of alcC demonstrated that alc transcription extends approximately 3.6 kb further downstream from the alcC coding region, suggesting the cotranscription of additional, uncharacterized alcaligin system genes. Originally published Journal of Bacteriology, Vol. 180, No. 4, Feb 1998
Keywords: Bordetella pertussis; Iron environment; Alcaligin